1996
DOI: 10.1111/j.1532-5415.1996.tb05641.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Four Methods for the Diagnosis of Respiratory Syncytial Virus Infection in Older Adults

Abstract: Rapid antigen tests for the diagnosis of RSV in older persons should be used with caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 10 publications
2
48
0
3
Order By: Relevance
“…RSV is the main cause of childhood viral ARI [28] and has been detected among other respiratory viruses, mainly influenza A, rhinovirus, coronaviruses and parainfluenza viruses, in exacerbations of COPD [29][30][31][32]. For older adults it has been shown that the diagnosis of RSV with less sensitive tests can be difficult and are not always reliable, leading to the complementary use of different methods for RSV detection [33,34]. The main advantages of the RSV-A specific qPCR assay are high specificity and sensitivity as well as its exact quantification and reproducibility.…”
Section: Discussionmentioning
confidence: 99%
“…RSV is the main cause of childhood viral ARI [28] and has been detected among other respiratory viruses, mainly influenza A, rhinovirus, coronaviruses and parainfluenza viruses, in exacerbations of COPD [29][30][31][32]. For older adults it has been shown that the diagnosis of RSV with less sensitive tests can be difficult and are not always reliable, leading to the complementary use of different methods for RSV detection [33,34]. The main advantages of the RSV-A specific qPCR assay are high specificity and sensitivity as well as its exact quantification and reproducibility.…”
Section: Discussionmentioning
confidence: 99%
“…However, elderly or immunocompromised adults may develop severe RSV infection (4,5,23). In contrast to children, diagnosis in adults is often difficult due to the insensitivity of viral culture (7). This is likely due to thermolability of the virus and low titers of virus shed by adults and may also be due to the presence of preexisting nasal antibody in clinical specimens resulting in in vitro neutralization.…”
mentioning
confidence: 97%
“…De las 114 muestras restantes con sospecha de IRV e IFD negativa para virus respiratorios, 17 (14,9%) resultaron positivas para VRS por TR-RPC en tiempo real, todos tipo B. Esto representa un aumento de 121% en la capacidad de diagnóstico de VRS en ese momento. En la Figura 1 se muestra la distribución variable de la positividad de los exámenes (IFD y TR-RPC tiempo real), según la semana epidemiológica (Figura 1A), observándose un paralelismo entre los resultados observados en los pacientes internados con prueba positiva y la detección del virus en la comunidad en las mismas semanas de vigilancia epidemiológica para VRS en Santiago (Figura 1B) 12 .…”
Section: Resultsunclassified
“…Según datos de vigilancia epidemiológica de virus respiratorios de la ciudad de Santiago 12 , durante el período de estudio se registraba una baja progresiva de casos de VRS, posterior a su mayor actividad ocurrida en la semana 29; este comportamiento fue similar al observado en la curva obtenida al graficar las muestras positivas por semana epidemiológica, incluyendo IFD más RPC positivas; este hecho nos ratifica que, entre adultos hospitalizados, se refleja la actividad de VRS presente en la comunidad 2 .…”
Section: Discussionunclassified